Gas‐Phase Selective Oxidation of Methane into Methane Oxygenates - Xu, Zhen Chao; Park, Eun Duck (Catalysts, 2022)
Methane is an abundant resource and its direct conversion into value‐added chemicals has been an attractive subject for its efficient utilization. This method can be more efficient than the present energy‐intensive indirect conversion of methane via syngas, a mixture of CO and H2. Among the various approaches for direct methane conversion, the selective oxidation of methane into methane oxygenates (e.g., methanol and formaldehyde) is particularly promising because it can proceed at low temperatures. Nevertheless, due to low product yields this method is challenging. Compared with the liquid‐phase partial oxidation of methane, which frequently demands for strong oxidizing agents in protic solvents, gas‐phase selective methane oxidation has some merits, such as the possibility of using oxygen as an oxidant and the ease of scale‐up owing to the use of heterogeneous catalysts. Herein, we summarize recent advances in the gas‐phase partial oxidation of methane into methane oxygenates, focusing mainly on its conversion into formaldehyde and methanol.
Keywords: Formaldehyde; Methane; Methanol; Partial oxidation; Promoter; Support